2013
DOI: 10.1128/aac.02037-12
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Emergence of Echinocandin Resistance during Candida kefyr Fungemia Treatment with Caspofungin

Abstract: e Echinocandin drugs are widely used for the treatment of candidemia. Resistance is considered rare, and only a few cases of breakthrough candidiasis in patients receiving echinocandin have been reported worldwide. We report here for the first time a Candida kefyr isolate that acquired echinocandin resistance very rapidly after the initiation of caspofungin treatment for candidemia. We characterized the FKS gene mutation responsible for the resistance via the comparison of isolates sampled before and during tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
42
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 15 publications
(7 reference statements)
1
42
1
1
Order By: Relevance
“…More detailed study of these isolates (J. F. Staab, D. Neofytos, P. Rhee, C. Jimenez-Ortigosa, S. X. Zhang, D. S. Perlin, and K. A. Marr, submitted for publication) documented variable MICs to different echinocandins. Also, other investigators have observed C. kefyr resistance to echinocandins developing rapidly under treatment (37). Although our risk factor analysis identified administration of azoles or amphotericin B to be protective against C. kefyr colonization, it appears that C. kefyr has the propensity to develop resistance to all classes of antifungals, based on the MICs observed in the IC C. kefyr isolates in our study.…”
Section: Discussioncontrasting
confidence: 61%
“…More detailed study of these isolates (J. F. Staab, D. Neofytos, P. Rhee, C. Jimenez-Ortigosa, S. X. Zhang, D. S. Perlin, and K. A. Marr, submitted for publication) documented variable MICs to different echinocandins. Also, other investigators have observed C. kefyr resistance to echinocandins developing rapidly under treatment (37). Although our risk factor analysis identified administration of azoles or amphotericin B to be protective against C. kefyr colonization, it appears that C. kefyr has the propensity to develop resistance to all classes of antifungals, based on the MICs observed in the IC C. kefyr isolates in our study.…”
Section: Discussioncontrasting
confidence: 61%
“…Fifth, if multiple mutations were necessary for drug resistance, antifungal adaptation that required a particular combination of mutations would be expected to be extremely rare. Taken together, several lines of evidence besides our CFW study show that drug resistance based on protein function can emerge quickly given the appropriate selection pressure (11,13,33), consistent with single-gene mutations. In contrast, resistance to polyenes that target ergosterol distribution, rather than its synthesis, has been relatively durable, although even it has been overcome recently (33).…”
Section: Discussionsupporting
confidence: 63%
“…They did not identify the mutated genes, probably due to factors mentioned above. Second, echinocandin resistance mutations are typically at single sites in FKS1 (10)(11)(12). Third, single mutations in Erg11 lead to resistance to azoles (32).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations